If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 108 + -3x = 3x + 12 Reorder the terms: 108 + -3x = 12 + 3x Solving 108 + -3x = 12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 108 + -3x + -3x = 12 + 3x + -3x Combine like terms: -3x + -3x = -6x 108 + -6x = 12 + 3x + -3x Combine like terms: 3x + -3x = 0 108 + -6x = 12 + 0 108 + -6x = 12 Add '-108' to each side of the equation. 108 + -108 + -6x = 12 + -108 Combine like terms: 108 + -108 = 0 0 + -6x = 12 + -108 -6x = 12 + -108 Combine like terms: 12 + -108 = -96 -6x = -96 Divide each side by '-6'. x = 16 Simplifying x = 16
| 3x(x-4)(2x+5)=0 | | x-9=-1+8 | | y=7(14)+34 | | -6(6v+4)=36-5v | | 6.7(x-3)=-0.3x+14.9 | | -4=12 | | -90=-8(3n+5)-2 | | 8n+32=-4(-3n-8) | | 5(x+1)=4(x+1) | | 174-4x=23x+4 | | N-(n+4)=-4n+28 | | 5-7x=129-35x | | (14p^4-17p^2+14p-3)+(2p-3)= | | 5n+12=9n-12 | | 9z-10=-3+2a+7 | | x^2+8=6 | | -(-4)=2x+6 | | -3-9=10x+8-9x | | 2x^4+15x^2+25=0 | | -22-7k=8-6(5-6k) | | 6x-25=2x+15 | | 3(4x-6)+8=5x+4 | | 5x+7-4x=14 | | x+7=3x-3 | | -3(-3-7)=5a+37 | | -4x-4x=78-6 | | 2x+5=x+55 | | 6(6x+7)=-36-3x | | m^2-7m+14=0 | | -8-4m=-2(m+4) | | -9+2x=-8-3x | | 4y+2x=12 |